Fluxo de Potência Ótimo com Restrições da Curva de Capabilidade do Gerador Síncrono como um Problema de Otimização Convexa. - FERNANDES, Italo Gusmão (2018)
Optimal power flow (OPF) is a non-convex, nonlinear and hard to solve optimization problem. When the synchronous generator operational limits are not concerned, OPF solution may not be applicable in real scenarios, leading the machine to operate in current values above those acceptable for windings. The synchronous generator capability curve (SGCC) used in this work includes machines current and power limits, preventing operation in overheating or excessive mechanical stress situations. Convex relaxation methods allow the problem to be formulated and solved in a simpler way than the original formulation. In this work a solution methodology is proposed for OPF, including SGCC. Thus, the OPF is formulated as a second order conic programming problem (SOCP) through relaxation techniques applied in power flow equations, aiming total cost generator minimizing, subject to electrical constraints of network. The model also includes in the constraints a security approach to the lines concerning simple contingencies in the system. The proposed methodology was implemented in a MATLAB® computing environment and applied to 9-bus WSCC and 39-bus New England test systems. The simulations show the OPF applicability as an optimization tool for electric power systems, proving the relaxation process precision and the SGCC impacts when it is included in OPF.